Changes in jejunal mucosa after long-term feeding of germfree rats with gluten - Stĕpánková, R; Tlaskalová-Hogenová, H; Sinkora, J; Jodl, J; Fric, P (Scandinavian journal of gastroenterology, 1996)
BACKGROUND: Coeliac disease (CD) or gluten-sensitive enteropathy is a chronic gastrointestinal disease of children and adults. An experimental model using inbred germfree rats has been developed to study the effects of intragastric gliadin application on intestinal mucosa. METHODS: AVN strain Wistar rats (inbred F 87)-germfree were used. Gliadin was applied by intragastric probe from birth until day 63 (0.5-5 mg of gliadin per immunization). Intraepithelial lymphocytes (IEL) were separated from the jejunum, and surface marker characterization was performed using flow cytometry. Isolated IEL were labelled with fluorescein isothiocyanate and injected into control jejunal loops. After 1 h and 6 h the abdominal cavity was reopened. The samples of jejunum were fixed. RESULTS: Prolonged application of gliadin led to the shortening of jejunal villi, crypt hyperplasia, increased number of mitoses in the crypt epithelium, and increased number of IEL-characteristic CD8+, RGL-1+, and TcR alpha/beta +. Transfer of IEL separated from rats fed with gliadin into the intestinal loops of untreated rats led to tight junctions in the enterocytes of the intestinal loops. The IEL isolated from controls (albumin-treated) induced no mucosal changes in intestinal loops. CONCLUSION: These data suggest that IEL isolated from gliadin-treated rats transfer mucosal damage and that gluten-induced enteropathy has an autoimmune component.
Keywords: Animals; Serum Albumin; Humans; potkani Wistar; Jejunum; T-lymfocyty; lidé; střevní sliznice; zvířata; Flow Cytometry; sérový albumin; Cell Separation; Celiac Disease; jejunum; separace buněk; gliadin; průtoková cytometrie; Time Factors; časové faktory; Rats; Animals, Suckling; Rats, Wistar; Intestinal Mucosa; kojená zvířata; T-Lymphocytes; Gliadin; krysa rodu Rattus; gnotobiologické modely; celiakie; Germ-Free Life